(untitled) (Brazilian Geographical Journal, 2013)
The Brazilian Geographical Journal (BGJournal) is pleased to launch the scientific community our last a number consisting of articles, notes and book reviews with scientific contributions which focus on the areas of Botany, Ecology, Rural Geography, Urban Geography, Geomorphology and Paleontology. Disclosed studies on the natural and socio-spatial dynamics of Latin America and Europe. We thank all the authors who submitted their work, thus contributing to the dissemination of knowledge and dissemination of Earth Sciences and in scientific circles. Finally, we invite the entire academic community to continue submitting your work to our journal Geoscience.